Tuesday

March 3, 2015

March 3, 2015

Posted by **Daniel** on Friday, October 14, 2011 at 10:10pm.

y = cosx - sinx (pi, -1)

I found y'= -sinx - cosx

and used the equation of the tangent

y = mx +b

I input the values and get -1 - [(-sinx - cosx) * pi] = b

the answer says it is y = x - 1 - pi

I have no idea how the answer got that.

- calculus -
**bobpursley**, Friday, October 14, 2011 at 10:14pmm= -sinPI-cosPI=1

y= x+b

-1=PI+b

b= -PI-1

y=x-pi-1

**Answer this Question**

**Related Questions**

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Math - Im really struggling with these proving identities problems can somebody ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...

Math - Pre- Clac - Prove that each of these equations is an identity. A) (1 + ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

Ap Calc AB - Find the equation of the line normal to the curve at (0,0). (Normal...